Comparison of the distributions of ipsilaterally and contralaterally projecting corticocortical neurons in cat visual cortex using two fluorescent tracers - Segraves, MA (J Neurosci, 1985)
Using the retrograde fluorescent tracers Fast Blue and Diamidino Yellow we have studied the callosal and ipsilateral corticocortical connections between the cat's area 17/18 border region and the posteromedial lateral suprasylvian visual area (PMLS), as well as the callosal connections of each of these regions with its contralateral homologue. The main goal was to determine whether single cortical neurons project with branching axons to more than one cortical target. In addition, the double-labeling technique enabled us to examine, within a single section of cortical tissue, the relative distributions of neurons with different cortical targets. Most corticocortical neurons labeled in the area 17/18 border region and in area PMLS projected to only one of the cortical injection sites tested. When two callosal neuron types were labeled in the same area, no double-labeled neurons were found. When ipsilateral corticocortical and callosal neurons were labeled in combination, a few double-labeled neurons were found in both cortical regions examined. The most common type of double- labeled neuron was located in area PMLS and projected bilaterally to the area 17/18 border region. Our findings regarding the laminar distributions of ipsi- and contralaterally projecting neurons are in agreement with previous studies. In addition, we have found that, for callosal neurons within the upper layers of areas 17 and 18, neurons projecting to the contralateral area 17/18 border are located in the lower half of layer II/III and in upper layer IV, whereas neurons projecting to contralateral area PMLS are restricted to the lower portion of layer II/III. In addition, for callosal neurons within the deep layers of area PMLS, neurons projecting to contralateral area PMLS are located throughout layers V and VI, whereas neurons projecting to the contralateral area 17/18 border are restricted to layer VI. There are numerous other possible targets for axon collaterals not examined in this paper. However, the scarcity of neurons with multiple projections demonstrated in this study reflects the high degree of specificity of cortical connectivity. This anatomical organization may be the basis for a precise channeling of differential information at the single neuron level.